Legitimidade percebida sobre a reforma contábil em governos locais da América Latina: a perspectiva dos contadores - Frisancho, Gabriela Molina (2022)
The research analyzed the perception of normative legitimacy of local government accountants regarding the adoption of IPSAS in Latin America. The accounting reform has brought about changes in the public accounting sector that have comprised the IPSAS. In this process of convergence, countries have developed different strategies with a view to adopting new international standards. The literature has pointed out influential factors in the adoption process and has suggested the existence of additional factors not yet researched. A growing culture of rhetorical adoption is being replicated in Latin American countries and constant efforts are being made by national bodies leading the reform. Under the theoretical lens of normative legitimacy (normativity), a comparative analysis was carried out among seven Latin American countries. The results suggest that for a reform to take place, a simple change in accounting regulations is not enough. First, the accounting environment can affect the accountant's development when changes occur. Factors such as standardized accounting practices, charts of accounts, internal or outsourced software, composition of the accounting team, among others, must be taken into account in the process of adopting reforms (declaration, implementation, application). Second, the accountant's posture on reform matters, and the accountant's perceived legitimacy of the standard has a strong bearing on its success. Third, the support of the local high level, perception of monitoring and the presence of resources (humans, software) are relevant elements for the reform to occur, but they are effective only in the presence of perceived the norm as legitimate by the accountant. Even with the presence of these factors, if the accountant does not perceive the norm as legitimate, the adoption will be symbolic because the accountant will do the minimum force for its implementation and to "appear" to be adequate to the rules. The research suggests changing the format for diffusion the changes or new accounting policies. The current format is focused on guiding how to do it, leaving aside the diffusion of importance, that is, why to do it. So, a process of theorizing is necessary. There is a need for greater focus on spreading the message of the importance of change and not just disseminating guidelines to be followed. Additionally, the process would have to involve both accountants and staff, especially at the highest level, ensuring support and active participation in the IPSAS adoption process.